Nanofluidic chip on tube as standard leak elements. (January 2022) - Lin, Wenyu; Zhang, Huzhong; Xi, Zhenhua; Bi, Hailin; Luo, Yan; Wang, Kuibo; Cao, Qing; Wang, Xudi; Wu, Xiaobin
Highlights: Nanofluidic chip is prepared using MEMS lithography technology and SDB process. Reliable macro-micro connections are achieved through fusion bonding of glass tubes. Leak flow conductance is up to 10 −13 m 3 /s for He, N2 and Ar. Nanofluidic elements exhibit stable molecular flow in pressure range up to 10 5 Pa. The leak can be used for instrument calibration and microflow studies. Abstract: The nanofluidic chips with channels of 100-nm depth and 3-μm width were employed as molecular flow standard leak elements for vacuum technology applications in this paper. The nanofluidic chips are fabricated by MEMS technologies while the macro-micro connection is achieved using glass fusion bonding and standard Swagelok® Fitting. It is found that the choice of annealing temperature and holding time is a key issue regarding fusion bonding and the optimal processing parameters are 780 ℃, 5 min. Meanwhile, the sealing reliability of fusion bonding and the fitting connection is evaluated. Experiment shows that the flow conductance of the as-fabricated leak can reach 10 −13 m 3 ∙s −1 magnitude for He, N2 and Ar. This standard leak has the advantages of controlled dimensions, reliable connection, and constant flow conductance over a range of 10 5 Pa.